The Kid‐Short Marfan Score (Kid‐SMS) – an easy executable risk score for suspected paediatric patients with Marfan syndrome. (7th December 2012) - Mueller, Goetz C; Stark, Veronika; Steiner, Kristoffer; Weil, Jochen; von, Yskert; Mir, Thomas S
Abstract Aim Due to age‐dependent manifestations, diagnosis of Marfan syndrome (MFS) in children and adolescents is sophisticated. Although revised Ghent criteria is a major step forward, its utility in children is still restricted due to expensive and technically advanced diagnostics. As early diagnosis submits long‐term benefits concerning prognosis, the need of an appropriate diagnostic tool for risk stratification of suspected paediatric patients with Marfan is justified. Methods and results Sixty paediatric patients with Marfan were subject to a standardized diagnostic programme. All clinical symptoms of the revised Ghent nosology were analysed concerning age at first clinical manifestation, prevalence and likelihood ratio for MFS. Symptoms with early onset, high prevalence and high positive likelihood ratio were identified and combined for a risk score called Kid‐Short Marfan Score (Kid‐SMS). Three risk categories for suspicion of Marfan syndrome were developed. Finally, the Kid‐SMS was operated in 130 paediatric patients with suspected MFS. Kid‐SMS identified significantly more suspected patients with Marfan compared with Ghent nosology, revised Ghent and genetics alone without oversensitivity. Conclusion Whereas diagnosis of MFS in childhood is sophisticated, Kid‐SMS is a useful tool for risk stratification of suspected paediatric patients with Marfan by easy executable diagnostics, especially for paediatricians and paediatric cardiologists.